The Impact of Dominant Color in the Shopee Application's User Interface Design on User Focus Levels - Fathimah Fadiyah Salimah; Septi Mulia Putri; Badia Inaya Sazrade; Fathoni (The IJICS (International Journal of Informatics and Computer Science), 2026)
The design of mobile application interfaces plays a crucial role in shaping user experience, where color influences not only aesthetics but also user cognition and focus. This study aims to analyze the effect of the dominant orange color in the Shopee application interface on user focus levels. A quantitative correlational approach was employed, involving 32 respondents who completed a Likert-scale questionnaire, with data analyzed using SPSS. The results show a strong and statistically significant correlation between color perception and user focus (r = 0.681; p < 0.05), indicating that better evaluation of the dominant color is associated with higher focus levels. Furthermore, the coefficient of determination (R² = 0.464) reveals that nearly half of the variation in user focus is explained by color alone. These findings confirm that the dominant orange color enhances attention, supports sustained concentration, and improves navigation efficiency. This study highlights color as a key functional factor in optimizing user focus in mobile commerce applications.